2018
DOI: 10.1016/j.jfma.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Single allele Lmbrd1 knockout results in cardiac hypertrophy

Abstract: The results suggested that Lmbrd1 gene not only plays a significant role in mediating the energy homeostasis in cardiac tissue, it may also be a key factor in the regulation of cardiac function in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Interestingly, other compounds that are strongly linked with vitamin B12 deficiency-MMA have been recently identified as oncometabolites. MMA is a metabolite of methylmalonyl coenzyme A, and its increased levels result from impaired conversion to succinyl coenzyme A in a vitamin B12dependent manner [180]. A study published in 2020 by Gomes et al revealed that MMA levels increase in the serum of older individuals and may have a function as a mediator of tumor progression.…”
Section: Long-distance Consequences Of Vitamin B12 Deficiencymentioning
confidence: 99%
“…Interestingly, other compounds that are strongly linked with vitamin B12 deficiency-MMA have been recently identified as oncometabolites. MMA is a metabolite of methylmalonyl coenzyme A, and its increased levels result from impaired conversion to succinyl coenzyme A in a vitamin B12dependent manner [180]. A study published in 2020 by Gomes et al revealed that MMA levels increase in the serum of older individuals and may have a function as a mediator of tumor progression.…”
Section: Long-distance Consequences Of Vitamin B12 Deficiencymentioning
confidence: 99%
“…Generation of Lmbrd1 +/− mice has been described previously [8]. In brief, Lmbrd1 +/− mice in the background of C57BL/6J were generated by using Cre-LoxP system that allowed deletion of the exon 6 and 7 of the Lmbrd1 gene.…”
Section: Cultured Mouse Embryo Fibroblasts (Mefs)mentioning
confidence: 99%
“…In addition, Lmbrd1 heterozygous knockout causes cardiac hypertrophy in mice due to a significant increase in myocardial glucose uptake. The increase of glucose uptake is a consequence of constitutive activation of IR signaling pathway resulting from the retention of IR on the plasma membrane [8]. Furthermore, LMBD1 function is essential for the expression of fibroblast growth factor 8 to provide intact gastrulation and mesoderm formation during mouse embryogenesis [9].…”
Section: Introductionmentioning
confidence: 99%